The development of a new end-to-end Customer Relationship Management (CRM) approach for Jupiter Design - Cheng, Ya-Fang; Hann, David; Jones, Tim; Ogbemudia, Sarah (2006)
This report has been produced by a team of MBA students from Nottingham University Business School, with the remit of developing a new approach to end-toend Customer Relationship Management (CRM) for the client - Jupiter Design (Jupiter). During the past 12-years Jupiter has grown significantly in terms of both size and client base. To consolidate this growth, Jupiter has identified that it must maximise the revenue from its existing client base. The adoption of a CRM approach has been suggested as a possible solution.